A review of the boneti-group of the genus Coecobrya (Collembola: Entomobryidae) - Zhang, Feng; Man, Le Cong; Deharveng, Louis (Zootaxa, 2011)
The genus Coecobrya is divided here into tenebricosa- and boneti-groups, blind and with a large outer tooth on the unguiculus in the former, and eyed and with the outer edge of unguiculus smooth or serrate in the latter. All five species of boneti-group are reviewed here and their diagnostic characters compared in a table. Coecobrya. boneti (Denis) and C. tetrophthalma (Denis) from Vietnam, are redescribed based on examination of their types and of newly collected topotypes. A key to the species of boneti-group is provided.